Carbon dioxide emission decomposition along the gradient of economic development: The case of energy sustainability in the G7 and Brazil, Russia, India, China and South Africa. (11th November 2019) - Su, Weihua; Wang, Yuying; Streimikiene, Dalia; Balezentis, Tomas; Zhang, Chonghui
Abstract: The G7 and Brazil, Russia, India, China and South Africa (BRICS) nations have committed to greenhouse gas emission reduction according to targets set out in the Paris Agreement and Copenhagen Accord. The objective of this paper is to develop an index decomposition framework and apply it for comparison of the drivers behind carbon dioxide emission. The impact of economic and technological development on greenhouse gas emissions is assessed by applying the Kaya identity. The index decomposition analysis is carried out by applying the Shapley value. In this paper, we seek to compare the two groups of countries—G7 and BRICS—in regard to the underlying trends in the energy‐related carbon dioxide emission during 1990–2015. The comparison of these two groups for countries draws some light on the pathways of decarbonization of the economies in developing and developed countries. The time period covered spans over the sub‐periods of economic growth and decline. Energy intensity appeared as the major factor pushing the carbon dioxide emissions down in the developed countries (i.e., G7 group). The latter effect was much lower for the developing countries (i.e., BRICS group) and was offset by the affluence effect. Further development of the renewable energy is important for the developing countries in order to start exploiting the carbon factor effect.